Social choice: a framework for collective decisions and individual judgements within a cross-cultural society. - Comrie, Henri, Pierre (My University, 1995)
This discourse represents a searching process. Its outcomes are consciously unpredictable and open-ended. Its topic is influenced by spatial dilemma across the spectrum of South - African cities and the fact that opportunities of finding answers towards integration on a regional level has only now become desirable and feasible through national policy. During a period of heightened political awareness the need for integration and improved access has become a pressing issue which forces us to seek answers on our feet.( Abbreviation abstract )
A thesis submitted to the Faculty of Architecture, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree Master of Urban Design
Keywords: City planning--cross-cultural studies--South Africa--Nelspruit; Social choice; City planning--decision-making